Gestão da coleta de lixo no município de Apiaí - SP - Ribas, Daniele Santos (2011)
This work has as its theme the Management of Garbage Collection in Apiaí County, State of São Paulo. Its main objective is to analyze as it is done picking up trash in the city and through it, assess what benefits and harms brought by the garbage company and the government. If that means starting from the knowledge of how it occurs collection and disposal of solid waste will contribute ideas or propose alternatives and / or complementary results that enhance recycling and reuse of materials discarded by society. And this step, it is important to combine routine procedures for the awareness of society who through community campaigns, seek to reduce, recycle and reuse, whether in urban or rural area. And to achieve these goals the work was constructed through literature searches whose contributions are aligned to the case study that focuses on the city of Apiaí - SP, or the municipal government and some residents of rural and urban areas. By focusing on waste management this paper presents also a hallmark of environmental education, as search results coupled with satisfactory awareness of the individual and, as a result, society as a way of consolidating the critical and participatory citizenry, through which will contribute to eradicate or at least minimize the problems caused by poor waste management.